Neuromuscular adaptations to sprint interval training and the effect of mammalian omega-3 fatty acid supplementation - Lewis, E. J.; Stucky, F.; Radonic, P. W.; Metherel, A. H.; Wolever, T. M.; Wells, G. D. (European Journal of Applied Physiology, 2017)
Purpose: Sprint interval training (SIT) stimulates rapid metabolic adaptations within skeletal muscle but the nature of neuromuscular adaptions is unknown. Omega-3 polyunsaturated fatty acids (N-3 PUFA) are suggested to enhance neuromuscular adaptations to exercise. Methods: We measured the neuromuscular adaptations to SIT (Study-1) and conducted a placebo-controlled randomized double blinded study to determine the effect of N-3 PUFA supplementation on neuromuscular adaptations to SIT (Study-2). In Study-1, seven active men (24.4 ± 2.6 years, VO2 peak 43.8 ± 8.7 ml kg min-1) completed 2-weeks of SIT with pre- and post-training 10 km cycling time trials (TT). In Study-2, 30 active men (24.5 ± 4.2 years, VO2 peak 41.0 ± 5.1 ml/kg.min) were randomly assigned to receive N-3 PUFA (2330 mg/day) (n = 14) or olive oil (n = 16) during 2-weeks of SIT with pre- and post-training TTs. Four week post-training, a SIT session and TT were also performed. Change in neuromuscular function was assessed from resting twitches, quadriceps maximal voluntary contraction (MVC) force, and potentiated twitch force (Q tw). Results: Study-1 showed that SIT did not elicit significant neuromuscular adaptations. Study-2 showed that N-3 PUFA supplementation had no significant effect on neuromuscular adaptations. Training caused lower MVC force [mean ± SD; N-3 PUFA -9 ± 11%, placebo -9 ± 13% (p < 0.05 time)] and Q tw peripheral fatigue [N-3 PUFA -10 ± 19%, placebo -14 ± 13% (p < 0.05 time)]. TT time was lower after training in all groups [Study-1 -10%, Study-2 N-3 PUFA -8%, placebo -12% (p < 0.05 time)]. Conclusion: Two weeks of SIT improved TT performance in the absence of measurable neuromuscular adaptations. N-3 PUFA supplementation had no significant effect on SIT training adaptations.